Pemanfaatan Mesin Pengupas Kedelai untuk Meningkatkan Produksi UMKM Tempe - Agus Harijono; Moh. Nasir Hariyanto; pondi; AM MUFARRIH (CV. Multi Kreasi Media, 2022)
Tempe is one of the original foods that are much favored by the people of Indonesia. Malang is famous for having many tempe-making businesses, which are spread both in the city and district of Malang. MSME Sanan Sejahtera is one of the tempe producers located in Malang Regency, precisely in Watugede Village, Singosari District. The process of producing tempeh for SMEs is still done traditionally. Although this business has been running for quite a long time, this effort cannot be separated from various problems faced. The problems faced are the production capacity of tempe which is still very small, the price of soybean raw materials tends to rise, and the marketing of tempe is still not optimal. The purpose of this community service is to help increase the production capacity of tempe and tempe sales turnover. The solution to overcome this problem is to provide a soybean peeler machine to increase production capacity and provide knowledge about marketing through social media to increase sales. The results of this community service activity are proven to be able to increase the production and sales capacity of tempe, so that the welfare of the community can increase. The implementation of this PPM is carried out with the stages of field surveys, tool making, tool installation, and training on the use and maintenance of tools.